Ischemia-Triggered Glutamate Excitotoxicity From the Perspective of Glial Cells - Belov Kirdajova, Denisa; Kriska, Jan; Tureckova, Jana; Anderova, Miroslava (Frontiers in Cellular Neuroscience, 2020)
A plethora of neurological disorders share a final common deadly pathway known as excitotoxicity. Among these disorders, ischemic injury is a prominent leading cause of death and disability worldwide. Brain ischemia stems from cardiac arrest or stroke, both of which are responsible for insufficient blood supply to the brain parenchyma. Glucose and oxygen deficiency disrupt oxidative phosphorylation, which results in energy depletion and ionic imbalance, followed by cell membrane depolarization, calcium (Ca2+) overload, and extracellular accumulation of excitatory amino acid glutamate. If tight physiological regulation fails to clear the surplus of this neurotransmitter, a subsequent prolonged activation of glutamate receptors forms a vicious circle between elevated concentrations of intracellular Ca2+ ions and aberrant glutamate release, aggravating the effect of this ischemic cascade. The activation of downstream Ca2+-dependent enzymes has a catastrophic impact on nervous tissue leading to cell death, accompanied with the formation of free radicals, edema, and inflammation. After decades of "neuron-centric" approaches, recent research has also finally shed some light on the role of glial cells in neurological diseases. It is becoming more and more evident that neurons and glia depend on each other. Neuronal cells, astrocytes, microglia, NG2 glia, and oligodendrocytes all have roles in what is known as glutamate excitotoxicity. However, who is the main contributor to the ischemic cascade, and who is the unsuspecting victim? In this review, we summarize the so-far-revealed roles of cells in the central nervous system, with particular attention to glial cells in ischemia-induced glutamate excitotoxicity, its origins and consequences.